Vicious Circle Principle and Logic Programs with Aggregates. Issue 4 (21st July 2014) - GELFOND, MICHAEL; ZHANG, YUANLIN; Leuschel, Michael; Schrijvers, Tom
Abstract The paper presents a knowledge representation language <alternatives><inline-graphic xlink:href="ark:/27927/pgh1x7511wc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\mathcal{A}log$]]> </alternatives> which extends ASP with aggregates. The goal is to have a language based on simple syntax and clear intuitive and mathematical semantics. We give some properties of <alternatives><inline-graphic xlink:href="ark:/27927/pgh1x7511wc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\mathcal{A}log$]]> </alternatives>, an algorithm for computing its answer sets, and comparison with other approaches.